1987
DOI: 10.1135/cccc19872087
|View full text |Cite
|
Sign up to set email alerts
|

Acylated thioamides and related compounds as potential antituberculotics

Abstract: Some N-acylthioamides, thiobenzoylthioureas, and thiobenzoylureas were synthesized. The substances prepared were tested for their in vitro antimycobacterial activity. The structure of thiobenzoylureas was studied by synthetic and spectral methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A subsequent acylation of 1 with an acyl chloride could be carried out under basic conditions [5]. Recently, acylated thioamides (4) and related compounds have been shown to be potential antituberculotics [6]. In our reaction system, we have found that, by use of a catalytic amount of a very common tertial amine as a base, compounds 4 can be easily synthesized from the reaction of 1 with isocyanates.…”
Section: Resultsmentioning
confidence: 97%
“…A subsequent acylation of 1 with an acyl chloride could be carried out under basic conditions [5]. Recently, acylated thioamides (4) and related compounds have been shown to be potential antituberculotics [6]. In our reaction system, we have found that, by use of a catalytic amount of a very common tertial amine as a base, compounds 4 can be easily synthesized from the reaction of 1 with isocyanates.…”
Section: Resultsmentioning
confidence: 97%
“…However, little attention has been given to the corresponding heterocyclic carbothioamides. Pyridinyl and pyrazinyl carbothioamides have been reported as antituberculotics (Mollin et al, 1988), quinolinyl carbothioamides have been reported as plant microbiocides (Kluge et al, 1986), and benzofuranyl, pyridinyl, and furanyl carbothioamides have been reported as antitumor agents (Brouwer and Van Hes, 1986).…”
Section: Introductionmentioning
confidence: 99%